2021
DOI: 10.1039/d1bm00858g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and radio-labeled bio-hybrid scaffolds to promote and track in vivo the progress of bone regeneration

Abstract: This work describes the preparation, characterization and functionalization with magnetic nanoparticles of a bone tissue-mimetic scaffold composed of collagen and hydroxyapatite obtained thorough a biomineralization process. Bone remodeling takes place...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…For example, dopamine‐Fe (III) chelating nanoparticles were applied to monitor the state of implanted hydrogels and newborn cartilage in a real‐time and non‐invasive manner [159] . Furthermore, CT and MRI are employed jointly in the instance where commercial radiolabel ([99mTc] Tc‐MDP) was utilized to demonstrate metabolic activity and visualize fresh bone generation with exceptional precision, while superparamagnetic iron oxide nanoparticles administered at a specific dosage were implemented for echo SPECT/CT and MRI [160] . Figure 10a shows SPECT/CT obtained up to 5 weeks after surgery, demonstrating that the metabolic activity climbed to a maximum on day 7 and did not show any remarkable changes until day 20.…”
Section: Imaging Systems For Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, dopamine‐Fe (III) chelating nanoparticles were applied to monitor the state of implanted hydrogels and newborn cartilage in a real‐time and non‐invasive manner [159] . Furthermore, CT and MRI are employed jointly in the instance where commercial radiolabel ([99mTc] Tc‐MDP) was utilized to demonstrate metabolic activity and visualize fresh bone generation with exceptional precision, while superparamagnetic iron oxide nanoparticles administered at a specific dosage were implemented for echo SPECT/CT and MRI [160] . Figure 10a shows SPECT/CT obtained up to 5 weeks after surgery, demonstrating that the metabolic activity climbed to a maximum on day 7 and did not show any remarkable changes until day 20.…”
Section: Imaging Systems For Bone Regenerationmentioning
confidence: 99%
“…The 1st row: CT images on the skull of a Swiss Albino mouse model; and the 2nd row: fused SPECT/CT images at 3 h post‐injection with the bone imaging tracer [ 99m Tc] Tc‐MDP (ca. 2 mCi) [160] . Copyright 2021, Royal Society of Chemistry.…”
Section: Imaging Systems For Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…[94]. Campodoni et al [95] combined two magnetic NPs with a bone-repair scaffold to trace the process of bone regeneration in vivo. Radioactive tracers that were analysed and evaluated using SPECT/CT techniques showed that 0.75 wt% magnetic NPs mixed into bone scaffolds was sufficient to label bone tissues with magnetic NPs and monitor bone regeneration in vivo.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…For example, diagnostic markers can significantly improve the localization of biohybrid systems, as demonstrated by the CT imaging of biohybrid scaffold materials labeled with gold [85] and barium nanoparticles, [86] and MRI with manganese-loaded porphyrins, [87] ferritin derivatives, [88] and SPIONs. [46,89] Furthermore, 19 F-containing markers are often used for MRI labeling because fluorine is not usually found at significant concentrations in human soft tissues. Examples include fluorinated hydrogels [90] and vascular biohybrid scaffolds constructed from thermoplastic polyurethane and visualized by hybrid 1 H/ 19 F MRI.…”
Section: Noninvasive Imagingmentioning
confidence: 99%